Reef coral reproduction in the eastern Pacific: Costa Rica, Panamá, and the Galápagos Islands (Ecuador). VI. Agariciidae, Pavona clavus - Glynn, Peter W. (2011)
The reproductive ecology of the zooxanthellate reef coral Pavona clavus was investigated at several sites in Costa Rica, Panamá, and the Galápagos Islands (Ecuador) over the period 1985–2009. Pavona clavus displayed stable gonochorism as only five hermaphrodites were found in 590 samples. At four of five locations, sex ratios were skewed toward female dominance; however, at Saboga Island (Panamá) male colonies predominated. In Panamá, sexual maturity was observed in an estimated eight-year-old female colony, and several colonies of 10–20 years of age demonstrated gametogenesis. Sexual activity was observed at all study sites, but gamete development occurred in only 14–31% of colonies sampled sporadically. Seasonality of gametogenic activity occurred predominantly during the warm/wet season, June to August, at mainland sites (Caño Island, Costa Rica, and Gulfs of Chiriquí and Panamá, Panamá). This pattern was repeated in the Galápagos Islands, but mainly from March to May when seasonally high sea temperatures and rainfall prevailed there. Histological sampling and field observations indicated that spawning was centered around the full moon, most frequently on lunar day 17, and near sunset (1,800 h). Mean fecundity (mature ova cm−2 live tissue) estimates were significantly different for two sites and ranged from ~1,780 (Saboga Island, Gulf of Panamá, seasonally upwelling) to ~4,280 (Uva Is, Gulf of Chiriquí, non-upwelling). Assuming three annual spawning events colony−1 (August, September, October), extrapolation of minimum and maximum fecundities yield 5,340 and 12,840 ova cm−2 year−1. Seasonal, lunar, and diel spawning patterns in nine zooxanthellate species at Uva Island indicate asynchronous coral community spawning.